2008
DOI: 10.1158/1541-7786.mcr-07-0260
|View full text |Cite
|
Sign up to set email alerts
|

G-Quadruplex Stabilizer 3,6-Bis(1-Methyl-4-Vinylpyridinium)Carbazole Diiodide Induces Accelerated Senescence and Inhibits Tumorigenic Properties in Cancer Cells

Abstract: Carbazole derivatives that stabilized G-quadruplex DNA structure formed by human telomeric sequence have been designed and synthesized. Among them, 3,6-bis(1-methyl-4-vinylpyridinium)carbazole diiodide (BMVC) showed an increase in G-quadruplex melting temperature by 13°C and has a potent inhibitory effect on telomerase activity. Treatment of H1299 cancer cells with 0.5 Mmol/L BMVC did not cause acute toxicity and affect DNA replication; however, the BMVC-treated cells ceased to divide after a lag period. Hallm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 47 publications
2
31
0
1
Order By: Relevance
“…3B). Under the BMVC or BMVC4 conditions, no apparent cytotoxic effect was observed for up to 6 days (19,20). These results indicate that G-quadruplex stabilizers could reduce the expression of WNT1.…”
Section: Bmvc and Bmvc4 Repressed Wnt1 Expression Through Stabilizingmentioning
confidence: 72%
See 2 more Smart Citations
“…3B). Under the BMVC or BMVC4 conditions, no apparent cytotoxic effect was observed for up to 6 days (19,20). These results indicate that G-quadruplex stabilizers could reduce the expression of WNT1.…”
Section: Bmvc and Bmvc4 Repressed Wnt1 Expression Through Stabilizingmentioning
confidence: 72%
“…Previously, we characterized two carbazole derivatives, BMVC and BMVC4 ( Fig. 2A), that bound and stabilized the G-quadruplex structures formed by both human telomeric DNA sequences and the quadruplex-forming sequence located at the c-myc promoter (19,20). These two compounds were employed here to determine whether they could bind and stabilize the G-quadruplex structure formed by the G-rich sequence of WNT1 promoter.…”
Section: Bmvc and Bmvc4 Repressed Wnt1 Expression Through Stabilizingmentioning
confidence: 99%
See 1 more Smart Citation
“…Other Gquadruplex ligands, such as TMPyP4, cause G2/M phase arrest in MCF7 cells at subcytotoxic concentrations (Izbicka et al, 1999). Multiple effects on cell-cycle progression, such as activation of S-phase checkpoint and increase of M-phase, can also occur (Pennarun et al, 2005), as well as S-and G2/M phase arrest (Leonetti et al, 2004;Huang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…When in complex with telomere sequences, BMVC increases the melting temperature of G4 structure of telomere, 22,23 accelerates telomere length shortening, inhibits proliferation of cancer cells, and functions as a potential anticancer agent. 24 Recently, Neidle et al 20 found that the 3,6,9-trisubstituted acridine derivatives can significantly inhibit telomerase activity over 3,6-disubstituted derivatives. For example, a trisubstituted acridine compound, BRACO-19, is a well-known G4 stabilizer and telomerase inhibitor.…”
Section: Introductionmentioning
confidence: 99%